1973
DOI: 10.1901/jaba.1973.6-435
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFICACY OF STIMULUS FADING AND CONTINGENCY MANAGEMENT IN THE TREATMENT OF ELECTIVE MUTISM: A CASE STUDY1

Abstract: Stimulus fading techniques were compared to those of contingency management in the treatment of a 6-yr-old, electively mute girl. Experimental periods consisted of the mother rewarding the child for verbal and motor responses to scheduled tasks, while a stranger slowly entered the room and then gradually administered the task items as mother left the room. A timeout contingency for non-response to task items was also employed. Control periods consisted of a stranger administering the same tasks to the child un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
14
0

Year Published

1977
1977
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…Both Kratochwill 283 (1981) and Labbe and Williamson (1984) conducted comprehensive reviews of the literature, and indicated that a variety of treatment methods have been tried; also see Cline and Baldwin (1994) and Hadley (1994) for recent reviews. Behavioral treatments have included the use of stimulus fading (e.g., Conrad et al 1974, Wulbert et al 1973), contingency management (e.g., Williamson et al 1977), avoidance conditioning (e.g., Van der Kooy and Webster 1975), in vivo desensitization (e.g., Rasbury 1974), shaping procedures (e.g., Blake and Moss 1967), and modeling and self-modeling techniques (e.g., Pigott and Gonzales 1987). Though successful, these behavior therapy procedures have been questioned because of: (1) a lack of data on the maintenance or generalization of speech behavior, (2) the lack of information on spontaneous speech, and (3) their high cost and the intense use of professional time.…”
mentioning
confidence: 99%
“…Both Kratochwill 283 (1981) and Labbe and Williamson (1984) conducted comprehensive reviews of the literature, and indicated that a variety of treatment methods have been tried; also see Cline and Baldwin (1994) and Hadley (1994) for recent reviews. Behavioral treatments have included the use of stimulus fading (e.g., Conrad et al 1974, Wulbert et al 1973), contingency management (e.g., Williamson et al 1977), avoidance conditioning (e.g., Van der Kooy and Webster 1975), in vivo desensitization (e.g., Rasbury 1974), shaping procedures (e.g., Blake and Moss 1967), and modeling and self-modeling techniques (e.g., Pigott and Gonzales 1987). Though successful, these behavior therapy procedures have been questioned because of: (1) a lack of data on the maintenance or generalization of speech behavior, (2) the lack of information on spontaneous speech, and (3) their high cost and the intense use of professional time.…”
mentioning
confidence: 99%
“…Selective mutism refers to speech that occurs only in the presence of selected or restricted stimuli (Wulbert, Nyman, Snow, & Owen, 1973). The stimulus may be a person, such as an immediate family member, or a setting, such as the home environment.…”
mentioning
confidence: 99%
“…Lipton (1980), for example, used a combined stimulus fading, shaping, and contingency management program to elicit speech in a 6-year-old. Stimulus fading has also been paired with reinforcement (Conrad, Delk, & Williams, 1974;Reid et al, 1967), shaping (Norman & Broman, 1970), and time-out (Wulbert et al, 1973). Piersel and Kratochwill (198 1) used contingency management with extinction and positive and negative reinforcement in the treatment of two preschoolers.…”
mentioning
confidence: 99%
“…Procedural timeout has been used, with some success, to manage a variety of behaviors in applied environments: toileting (Azrin and Fox, 1971; Giles and Wolf, 1966), assaults by delinquent youths (Burchard and Tyler, 1965;Tyler and Brown, 1967), autistic behavior (Risley and Wolf, 1967), aggression (Clark, Rowbury, Baer, and Baer, 1973;Hamilton, Stephens, and Allen, 1967;LeBlanc, Busby, and Thomson, 1973;Sloane, Johnston, and Bijou, 1967;Vukelich and Hake, 1971), inappropriate speech (Hewett, 1965;Lahey, McNees, and McNees, 1973;McReynolds, 1969), oppositional and inappropriate social behaviors (Birnbrauer, Wolf, Kidder, and Tague, 1965;Nordquist, 1971;Pendergrass, 1972;Ramp, Ulrich, and Dulaney, 1971;Sajwaj, Twardosz, and Burke, 1972;Wahler, 1969), elective mutism (Wulbert, Nyman, Snow, and Owen, 1973), and unattractive eating (Barton, Guess, Garcia, and Baer, 1970).…”
mentioning
confidence: 99%